Cataloging the world Paul Otlet and the birth of the information age - Wright, Alex 1966-; Henderson, Kathrine A. 1965-.; Hauptman, Robert 1941- (Oxford New York, NY Oxford University Press, 2014)
"The dream of universal knowledge hardly started with the digital age. From the archives of Sumeria to the Library of Alexandria, humanity has long wrestled with information overload and management of intellectual output. Revived during the Renaissance and picking up pace in the Enlightenment, the dream grew and by the late nineteenth century was embraced by a number of visionaries who felt that at long last it was within their grasp. Among them, Paul Otlet stands out. A librarian by training, he worked at expanding the potential of the catalogue card -- the world's first information chip. From there followed universal libraries and reading rooms, connecting his native Belgium to the world -- by means of vast collections of cards that brought together everything that had ever been put to paper. Recognizing that the rapid acceleration of technology was transforming the world's intellectual landscape, Otlet devoted himself to creating a universal bibliography of all published knowledge. Ultimately totaling more than 12 million individual entries, it would evolve into the Mundaneum, a vast "city of knowledge" that opened its doors to the public in 1921. By 1934, Otlet had drawn up plans for a network of "electric telescopes" that would allow people everywhere to search through books, newspapers, photographs, and recordings, all linked together in what he termed a réseaumondial: a worldwide web. It all seemed possible, almost until the moment when the Nazis marched into Brussels and carted it all away. In Cataloging the World, Alex Wright places Otlet in the long continuum of visionaries and pioneers who have dreamed of unifying the world's knowledge, from H.G. Wells and Melvil Dewey to Ted Nelson and Steve Jobs. And while history has passed Otlet by, Wright shows that his legacy persists in today's networked age, where Internet corporations like Google and Twitter play much the same role that Otlet envisioned for the Mundaneum -- as the gathering and distribution channels for the world's intellectual output. In this sense, Cataloging the World is more than just the story of a failed entrepreneur; it is an ongoing story of a powerful idea that has captivated humanity from time immemorial, and that continues to inspire many of us in today's digital age"--Provided by publisher
The libraries of Babel -- The dream of the labyrinth -- Belle Epoque -- The microphotic book -- The Index Museum -- Castles in the air -- Hope, lost and found -- Mundaneum -- The collective brain -- The radiated library -- The intergalactic network -- Entering the stream
Includes bibliographical references (pages 311-335) and index
Keywords: Otlet, Paul -- 1868-1944.; Mundaneum -- History; Mundaneum; Bibliographers -- Belgium -- Biography; Universal bibliography; Documentation; Classification -- Books; Information organization -- History; World Wide Web -- History; Electronic books